Signaling pathways in liver fibrosis - BAHAR, ASLI NUR (My University, 2023)
Liver fibrosis is a disease characterized by activation of hepatic stellate cells (HSCs) and excessive accumulation of extracellular matrix (ECM) components that destroy the physiological structure of the liver. Liver fibrosis contributes to the increasing prevalence and severity of chronic liver diseases. If liver fibrosis, which is of great clinical importance, is not treated, it ends with cirrhosis, which is characterized by fatal and intense complications. Cirrhosis can progress to hepatocellular carcinoma. Although fibrosis was previously thought to be an irreversible process, studies have shown that because of the liver\"s high regenerative ability, regression and return to normal architecture is higher than in other tissues, even in advanced disease.Targeting signaling pathways that cause fibrosis and anti-fibrotic therapies are needed to prevent the progression of liver disease and the development of hepatocellular carcinoma (HCC). Activation of HSCs and transforming growth factor beta (TGF-beta), Wnt/beta-catenin signaling pathways and interactions play an important role in the pathogenesis of the disease. Sirtuins (SIRT) belong to the sirtuin family of Nicotinamide Adenine Dinucleotide, (NAD+) dependent protein deacetylases and are involved in many important cellular biological processes, including the inflammatory response, oxidative stress, and fibrosis. Sirtuin family has been shown to be involved in the regulation of fibrosis signaling pathways and in the cellular and molecular mechanisms of liver fibrosis. In this review, we aimed to summarize current knowledge about the signaling pathways that trigger differentiation, profibrotic activation of myofibroblasts and cause liver fibrosis that can be modulated by sirtuins.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Hepatic stellate cell; liver fibrosis; sirtuin; TGF-; Wnt; -catenin; BETA-CATENIN; FIBROBLAST ACTIVATION; SIRTUIN 1; INHIBITION; MECHANISMS; MELATONIN; TARGET; INJURY; ROLES; MICE